INNOVATIVE METHODS OF ORGANIZING SURGICAL EDUCATION - Yusupova Sitora Sanzharova (Modern American Journals, 2025)
This research addresses the problem of optimizing the surgical education process through modern technology. The study analyzes the effectiveness of innovative teaching methods using the example of wisdom teeth extraction (third molar extraction), a common but high-risk procedure in oral and maxillofacial surgery. The focus is placed on approaches such as Virtual Reality (VR) and Augmented Reality (AR) simulation systems, high-fidelity 3D models, and telementoring. The objective of the research is to determine the impact of these innovations on trainees' safe acquisition of technical skills and their ability to improve clinical decision-making. The findings of the work enable the formulation of specific recommendations for enhancing the quality of surgical education and ensuring patient safety in practice.
Keywords: Surgery, Third Molars, Extraction, Malposition, Impaction, Simulation, Virtual Reality (VR), Augmented Reality (AR).